Spatial Readings and Linguistic Landscapes. - Bako, Alina (Cambridge Scholars Publishing, 2022)
Talking about space in literature and linguistics is a major challenge, not only for experts in the field of the humanities, but also for the broader public, searching for orientation clues on the vast book market. This volume offers a selection of studies which, even though reliant on shared instruments, apply these to different geographical spaces, uniting along an imaginary axis the East and the West, advancing challenging, serious and innovative analyses of prose, dramatic and film texts, belonging to literatures from various countries, but also references to the phenomenon of migration se.